Applicability of a Lactobacillus amylovorus strain as co-culture for natural folate bio-enrichment of fermented milk - Laiño, Jonathan Emiliano (2014)
The ability of 55 strains from different Lactobacillus species to produce folate was investigated. In order to evaluate folic acid productivity, lactobacilli were cultivated in the folate-free culture medium (FACM). Most of the tested strains needed folate for growth. The production and the extent of vitamin accumulation were distinctive features of individual strains. Lactobacillus amylovorus CRL887 was selected for further studies because of its ability to produce significantly higher concentrations of vitamin (81.2 ± 5.4. μg/L). The safety of this newly identified folate producing strain was evaluated through healthy experimental mice. No bacterial translocation was detected in liver and spleen after consumption of CRL887 during 7 days and no undesirable side effects were observed in the animals that received this strain. This strain in co-culture with previously selected folate producing starter cultures (Lactobacillus bulgaricus CRL871, and Streptococcus thermophilus CRL803 and CRL415) yielded a yogurt containing high folate concentrations (263.1 ± 2.4. μg/L); a single portion of which would provide 15% of the recommended dietary allowance. This is the first report where a Lactobacillus amylovorus strain was successfully used as co-culture for natural folate bio-enrichment of fermented milk.